2020
DOI: 10.1111/1440-1681.13359
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biological activity and electrochemistry studies of iron(III) complex with curcumin‐oxime ligand

Abstract: Iron overload is a key target in drug development. This study aimed to investigate the coordination of Fe(III) ions with a curcumin-oxime ligand that may be used in the treatment of iron overload. The synthesis of the curcumin-oxime ligand and curcumin-oxime-Fe(III) complex were successfully made and characterized in its solid-state and solution-state using FT-IR, UV-Vis, elemental analysis, and 1 H-NMR. However, in this study, we investigated the apoptotic effects of the curcumin-oxime Fe (III) complex on SW4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Curcumin molecule has been reported to be the active site involved in the chelation of iron. It has chemical properties consistent with iron chelator activity [42][43][44]. This study aimed to investigate the effect of curcumin on iron overload in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin molecule has been reported to be the active site involved in the chelation of iron. It has chemical properties consistent with iron chelator activity [42][43][44]. This study aimed to investigate the effect of curcumin on iron overload in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, when iron is present in excess, iron-mediated oxidative stress occurs. In the presence of molecular oxygen generating oxygen-derived free radicals such as hydroxyl radicals, the highly reactive hydroxyl radicals attack the cell membrane, destroying DNA base sequences and sugar groups [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions were drawn for the Fe 3+ -CU-oxime complex. The authors suggested that CU and CU-oxime may be used to treat iron overload [146].…”
Section: Cu Interaction With Metal Ionsmentioning
confidence: 99%
“…Since oximes, including derivatives of 11 H -indeno[1,2- b ]quinoxalin-11-ones and related tryptanthrin analogs, could form complexes with different metal ions, and the ion-chelating properties of ligands can alter to their biological activities [ 38 , 39 , 40 ], we hypothesized that other salts of IQ-1 may lead to a change in therapeutic potential of the resulting ion complexes. In particular, we evaluated lithium salts of IQ-1 because Li + is also a promising candidate for the treatment of ischemic stroke [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%